Gene Loss, Pseudogenization in Plastomes of Genus Allium (Amaryllidaceae), and Putative Selection for Adaptation to Environmental Conditions - Scobeyeva, Victoria A.; Artyushin, Ilya V.; Krinitsina, Anastasiya A.; Nikitin, Pavel A.; Antipin, Maxim I.; Kuptsov, Sergei V.; Belenikin, Maxim S.; Omelchenko, Denis O.; Logacheva, Maria D.; Konorov, Evgenii A.; Samoilov, Andrey E.; Speranskaya, Anna S. (Frontiers in Genetics, 2021)
The genes present in chloroplast genomes (plastomes) play fundamental roles for the photosynthetic plants. Plastome traits could thus be associated with abiotic characteristics of habitats. Most chloroplast genes are highly conserved and are used as phylogenetic markers for many families of vascular plants. Nevertheless some studies revealed signatures of positive selection in chloroplast genes of many plant families including Amaryllidáceae. We have sequenced plastomes of the following ten Allium species: A. zebdanense, A. moly, A. victorialis, А. macleanii, A. nutans, A. obliquum, A. schoenoprasum, A. pskemense, A. platyspathum, A. fistulosum, A. semenovii as well as representative species of outgroup Allioideae, Nothoscordum bivalve (Tribe Leucocoryneae). In this work we provide our interpretation of Allium plastome genes' annotations. Also we found that Allium plastomes could demonstrate significant intraspecific variation, perhaps due to mistakes in taxonomy identification of specimens or their cross-hybridization during cultivation. Using chosen Allium species we estimated the integral evolutionary rate, counted SNPs and indels per nucleotide position as well as compared pseudogenization events in the species of three main phylogenetic lines of genus Allium to estimate whether they are potentially important for plant physiology or just follow the phylogeny of the genus. We examined totally 15 species of Allium: four of 1st evolutionary line, two of 2nd evolutionary line and nine of 3rd evolutionary line. We found that rps2, infA, rps16 genes have lost their functionality multiple times in different species (regularly evolutionary events), while the pseudogenization of other genes was stochastic events. We found that the “normal” or “pseudo” state of rps2, infA, rps16 genes correlates well with the evolutionary line of genus the species belongs to. We found some evidence of positive selection in ndh, matK, accD and some other genes. Taking into account known mechanisms of coping with excessive light by cyclic electron transport, we can hypothesize that adaptive evolution in genes, coding subunits of NADH-plastoquinone oxidoreductase could be driven by abiotic factors of high mountains, especially by intensive light and UV radiation.